(untitled) (Bioscience Journal, 2016)
The storage of grains under technical conditions in favorable environment ensures grain quality and regulates the supply of raw material for food production. For this reason, the objective of this study was to evaluate the different forms of storage (aerated silo, non-aerated silo, silo bags and airtight) of grains produced in the Brazilian cerrado, over time (zero, three and six months), for different physical qualities of maize (normal grains, whole grains and broken grains). The research was conducted at the Federal University of Mato Grosso do Sul (UFMS), Chapadão do Sul Campus (CPCS), Grain Postharvest Laboratory. To determine the physical-chemical quality and the physical properties of grains over six months, samples were taken from the stored lots. Analysis of variance and comparison of means by Tukey’s test were conducted at 5% probability. The six-month storage time was the main factor contributing to the reduction of the quality of maize grains. Storage alternatives with aeration, non-aeration, bags and airtight environment did not influence the physical properties of maize grains. The broken maize grains showed the worst physical and chemical quality during storage time, while the batch of whole corn grains differ in quality during storage. It was concluded that airtight storage and storage in aerated silos were the conditions that best preserved the physical and chemical quality of maize grains over time.